A polyprodrug-based nanoplatform for cisplatin prodrug delivery and combination cancer therapy. Issue 93 (5th November 2019) - Lin, Chunhao; Tao, Yiran; Saw, Phei Er; Cao, Minghui; Huang, Hai; Xu, Xiaoding
Abstract : A robust mitoxantrone (MTO)-based polyprodrug nanoplatform was herein developed for systemic cisplatin prodrug delivery. This nanoplatform can concurrently deliver MTO and cisplatin to tumor cells and shows combinational inhibition of tumor growth. Abstract : Polyprodrug-based delivery technique is a fast-growing and effective strategy to improve the therapeutic efficacy of small molecule drugs. We herein developed a robust mitoxantrone (MTO)-based polyprodrug nanoplatform for systemic cisplatin prodrug delivery and combination cancer therapy. Our results show that this nanoplatform can concurrently transport MTO and cisplatin to tumor cells and significantly inhibit tumor growth.